The Effect of Wind Turbine Blade Material Type on Generated Electric Power - Sulaeman; Mitra Munandar; Suchy (Jurnal Teknik Mesin, 2021)
Electric power as an energy system has a very important role in the economic development of a country. Therefore, now many researches are conducting developments in energy generation research and one of them is the development of wind power plants or wind turbines. The purpose of this study was to determine the effect of the type of blade material used in wind turbines on the varying electrical power produced. The blade material used in this material is pine wood, fiberglass/epoxy composite and fiberglass/coconut fiber/epoxy. The tests carried out in this study were to measure the rotation of the rotor, measure the current, voltage and power for variations in wind speed. The wind speed used is 3 m/s 4 m/s 5 m/s 6 m/s. blade with fiberglass/epoxy/coconut fiber composite material gets high rotational results compared to other materials, at a wind speed of 6 m/s it can produce a rotation of 1241,156 rpm and the electrical power generated is 3,545 W.